IBD IN 2017 Development of therapy for and prediction of IBD - getting personal - Atreya, Raja; Siegmund, Britta (Nature Reviews Gastroenterology & Hepatology, 2018)
The central studies published in 2017 address novel IBD therapeutic strategies and prediction of the future disease course or response to a distinct therapy. Together, these studies contribute to the understanding of the regulation of mucosal homeostasis and at the same time serve to develop novel personalized treatment algorithms in patients in whom a severe disease course can be predicted.
EVALuna2:33885